Dynamic Analysis in Complex Economic Environments Essays in Honor of Christophe Deissenberg - Dawid, Herbert; Arifovic, Jasmina (Dynamic Modeling and Econometrics in Economics and Finance, 2021)
VIII, 239 p. 52 illus., 29 illus. in color.